EFFECT OF CREATIVE INDEPENDENCE PROBLEM SOLVING (CIPS)-BASED TRAINING MODULE ON PROFESSIONALISM OF RURAL INDONESIAN ELEMENTARY SCHOOL TEACHERS - Munastiwi, Erni; Yunos, Jailani Md; Alias, Maizam; Paimin, Aini Nazura (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2021)
Training is needed to ensure that teachers acquire the knowledge necessary to teach problem-solving skills. Furthermore, a specifically designed training material such as a module is especially needed when teachers work in remote areas with fewer resources. Meanwhile, six educational problem-solving skills development needs among teachers in rural Indonesian elementary schools were identified: teacher mentoring, self-actualization, competency, creativity, problem-solving, and independence. A training module was designed based on the needs which were assessed using the CIPS model. The study aimed to investigate the effects of the CIPS-based Training Module on the professionalism of elementary school teachers. In addition, the training module consists of five (5) stages, which include pre-entering, plan, setting, action, and evaluation. The quasi-experimental research was conducted on 63 elementary teachers from Nunukan and Sebatik Island, North Kalimantan, Indonesia, assigned randomly to either an experiment or a control group. Before the training, a pre-test was conducted, followed by training using the module for the experiment groups, and no training for the control group. Furthermore, a post-test was conducted in both groups to identify the effectiveness of the training module. The independent sample t-test showed that the experimental group obtained a higher mean score than the control group. In conclusion, the CIPS-based Training Module effectively develops professionalism in teaching problem-solving skills among the experimental group's elementary teachers. Meanwhile, the study implies that rural elementary teachers need to be prepared to teach problem-solving skills.